2021
DOI: 10.17014/ijog.8.2.233-253
|View full text |Cite
|
Sign up to set email alerts
|

Tholeiitic Basalt in Banyumas Basin (Kebasen, Central Java): The Evidence of Sedimentary Recycling Input and the Contribution of Oceanic Slab on Fore-arc Active Continental Margin (ACM) Magmatism

Abstract: The study of tholeiitic basalt is a general-classic study from geotectonic MORB, ocean island (OIB), continental rift, volcanic-arcs {IAB or Active Continental Margin (ACM)}. However, the geotectonic study of the tholeiitic volcanic-arcs is still unclear at the moment. In general, the arc tholeiitic is directly pointed to an island-arc volcanic, and the result of google search engine defines no existence of tholeiitic geochemistry which is formed from continental-arc volcanic (ACM). The problem lies in the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We consider that the origin magma of the porphyry intrusive rocks in the HLE prospect was a product of the subduction process of the Indian‐Australian oceanic plate beneath the southeastern margin of the Eurasian continental plate (Sundaland) (e.g., Hamilton, 1979; Katili, 1989). The presence of active continental margin (continental arc) along the Sunda magmatic arc was recently proposed in several studies (e.g., Gardner et al, 2013; Gertisser & Keller, 2003; Reubi et al, 2002; Fadlin et al, 2018, 2021). In addition, the whole‐rock geochemistry data of intrusive rocks from the HLE prospect, that is, Th/Ce ≥0.1 (Hawkesworth et al, 1997; He et al, 2008) and Zr/Y > 3 (Pearce, 1983) suggest sediment cycling input and continental crust signature, respectively (Figure 15).…”
Section: Discussionmentioning
confidence: 91%
“…We consider that the origin magma of the porphyry intrusive rocks in the HLE prospect was a product of the subduction process of the Indian‐Australian oceanic plate beneath the southeastern margin of the Eurasian continental plate (Sundaland) (e.g., Hamilton, 1979; Katili, 1989). The presence of active continental margin (continental arc) along the Sunda magmatic arc was recently proposed in several studies (e.g., Gardner et al, 2013; Gertisser & Keller, 2003; Reubi et al, 2002; Fadlin et al, 2018, 2021). In addition, the whole‐rock geochemistry data of intrusive rocks from the HLE prospect, that is, Th/Ce ≥0.1 (Hawkesworth et al, 1997; He et al, 2008) and Zr/Y > 3 (Pearce, 1983) suggest sediment cycling input and continental crust signature, respectively (Figure 15).…”
Section: Discussionmentioning
confidence: 91%
“…The volcanic member of the Halang Formation has similar characteristics as the Kumbang Formation, which is composed of andesitic lava and volcanic breccias. The calc‐alkaline to tholeiite magmatic affinity of the volcanic member of the Halang Formation (Fadlin et al, 2021; Hendratno & Monica, 2018) is commonly observed in volcanic arcs, including back‐arc, intra‐arc, or fore‐arc environments. K–Ar radiometric dating data are only available for a basaltic sill that cuts the shales of the Halang Formation in south‐south‐east Ajibarang (8.7 Ma) and an andesite intrusion in south‐west Majenang (5.1 Ma)—(Soeria‐atmadja et al, 1994); these dates are comparable to those obtained from the Kumbang Formation and the volcanic member of the Halang Formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the Somagede area (eastern part of the Banyumas basin), this volcanic‐facies member has a basaltic andesite composition of calc‐alkaline affinity and has two different origins, that is, sub‐aqueous, indicated by pillow lava structures and hyaloclastites, and aerial deposition, typified by lava flows and volcanic breccias (Hendratno & Monica, 2018). Whole‐rock geochemical analysis including major oxides, trace elements, and rare earth elements, combined with a petrographic study of basaltic pillow lava, member of the Halang Formation in the Kebasen area (eastern Banyumas basin) indicates it is a tholeiitic rock formed in an Active Continental Margin setting, involving sedimentary recycling (Fadlin, Godang, Hamzah, & Aditama, 2021). This suggests that the back‐arc volcanism that generated the Halang Formation incorporated continental components of Sundaland.…”
Section: Banyumas Basin At a Glancementioning
confidence: 99%
“…Geochemical and petrogenetic studies of volcanic rocks in Kebasen and surrounding areas have been previously carried out using major and trace element geochemistry approaches [2] [3]. However, studies on the volcanostratigraphy units, age of the volcanism, and paleo-environment have never been properly IOP Publishing doi:10.1088/1755-1315/1373/1/012047 2 conducted.…”
Section: Introductionmentioning
confidence: 99%